2013
DOI: 10.5771/0949-6181-2013-4-463
|View full text |Cite
|
Sign up to set email alerts
|

How future managers view societal culture: A comparison across seven CEE countries

Abstract: The purpose of our exploratory study is to describe the characteristics of a sample of Central and East European students in business and engineering from their cultural assumption perspective. The cluster-distinctive cultural practices are: High Power Distance, In-group and Institutional Collectivism, low Humane and Future Orientation. Expectations (ideals) record significant differences for all cultural dimensions, with the highest ones concerning Power Distance (desire to decrease), Performance Orientation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
2
3
0
Order By: Relevance
“…Overall, the highest mean values were reported for instrumental work values, followed by cognitive, social-altruistic and prestige. The above described values are consistent with cultural characteristics reported by Catana et al (2013) from the GLOBE student sample. When looking at career ambitions of business students, Čater et al (2013) found that business students are very interested in managerial careers (78.9 percent of Polish students and 49.5 percent of Slovenian) which hints high ambitions and expectations regarding their employer obligations in terms of career development.…”
Section: Managing Young Talent In Transition Economiessupporting
confidence: 88%
See 3 more Smart Citations
“…Overall, the highest mean values were reported for instrumental work values, followed by cognitive, social-altruistic and prestige. The above described values are consistent with cultural characteristics reported by Catana et al (2013) from the GLOBE student sample. When looking at career ambitions of business students, Čater et al (2013) found that business students are very interested in managerial careers (78.9 percent of Polish students and 49.5 percent of Slovenian) which hints high ambitions and expectations regarding their employer obligations in terms of career development.…”
Section: Managing Young Talent In Transition Economiessupporting
confidence: 88%
“…Our results also suggest that students in all three countries do not only have high expectations of employers, but are also willing to give a lot to employers, with the UK students leading by expressing significantly higher levels of loyalty, performance and development as employee obligations. In this way our results confirm the conclusion by Catana et al (2013) that young East Europeans perceive today's world as unpredictable and largely money-driven, so they are ready to work hard and gain additional education to 78 BJM 12,1 achieve tangible results in their work. Our results thus run against popular stereotype that young are expecting a lot and focusing on what they will get from employers and not willing to give much in return.…”
Section: Managing Young Talent In Transition Economiessupporting
confidence: 88%
See 2 more Smart Citations
“…It should also be emphasized that the countries under study are culturally composed of several different blocs (Catana et al , 2013) and that the mechanisms of economic and political governance were not exactly the same under communism (Kornai, 1992). Although the European Transitional Economies (ETEs), as Zupan and Kase (2005) refer to the CEE countries (including Russia), do not form a completely homogeneous group with regard to their HRM contexts and practices, there are enough similarities to allow for a conceptual model of strategic HRM in the ETEs to be developed.…”
Section: Introductionmentioning
confidence: 99%